2010
DOI: 10.15362/ijbs.v16i0.121
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Investigation of the Prevalence of Corporal Punishment of Children and Selected Co-occurring Behaviours in Households on New Providence, The Bahamas

Abstract: The purpose of this study is to examine the link between violence in homes, focusing on corporal punishment of children as a means of discipline, and other behaviours (including sexual abuse, illegal drug use, domestic violence, hitting of pets) which may be a cause for concern. This paper reports the results of a survey of 933 people and 12 case studies. Violence, physical or domestic, occurred in 62% of survey participants' homes. The survey indicates that in respondents' homes many children were physically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 27 publications
(21 reference statements)
2
14
0
Order By: Relevance
“…The ubiquitous nature of violence in Bahamian homes, combined with the smaller sample size may have prevented some other spanking-related associations noted in the American group from being detected in the Bahamian sample. Carroll et al (2011) and Brennen et al (2010) have demonstrated that corporal punishment is common in Bahamian households, a finding repeated here. Indeed, as reported by D'Avanzo (2008) this is a cultural norm in West Indian communities.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The ubiquitous nature of violence in Bahamian homes, combined with the smaller sample size may have prevented some other spanking-related associations noted in the American group from being detected in the Bahamian sample. Carroll et al (2011) and Brennen et al (2010) have demonstrated that corporal punishment is common in Bahamian households, a finding repeated here. Indeed, as reported by D'Avanzo (2008) this is a cultural norm in West Indian communities.…”
Section: Discussionsupporting
confidence: 76%
“…So for example there may be greater denial, or appreciation of these actions in the Bahamian group than in the American group. Brennen et al (2010) showed that residents of The Bahamas tend to consider what might be viewed as grievous bodily harm as physical abuse. Henning, Jones and Holdford (2005) noted differences in denial concerning domestic violence between males and females, so we cannot rule out the possibility of socially desirable responding, despite the confidential manner in which the data were collected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is another area of concern regarding dog welfare. Such attitudes may reflect the use of violence to discipline Bahamian children (Brennen, Carroll, Fielding, Miller, Adderley, & Thompson, 2010), and an old-fashioned attitude toward dog training (Lindsay, 2001). Moreover, pit bulls were most likely to be teased in training.…”
Section: Cultural Considerations and Carementioning
confidence: 99%
“…Similarly, a study conducted by researchers at the College of The Bahamas found that violence against children was regarded as abuse only when it resulted in severe physical harm to the victim (Brennen et al 2010). The 2011 Bahamas Secondary School Drug…”
mentioning
confidence: 99%